2019
DOI: 10.1089/wound.2018.0925
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Nutrition Care for Pressure Injuries in Hospitalized Patients

Abstract: It is estimated that up to 50% of hospitalized patients are malnourished. Malnutrition can lead to longer hospital stays, altered immune function, and impaired skin integrity and wound healing. Malnutrition has been found to be a significant factor influencing pressure injury (PI) risk and wound healing. While PI prevention requires multidimensional complex care using a variety of evidence-based strategies, hospitalized patients benefit from interventions that focus on improving oral nutrition to reduce PI ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 44 publications
(141 reference statements)
1
22
0
5
Order By: Relevance
“…Measures focusing on the prevention of pressure ulcers are necessary and multidimensional. The authors particularly emphasise the benefits of adequate nutritional care and report improved progress in pressure ulcer healing in patients subjected to such measures [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Measures focusing on the prevention of pressure ulcers are necessary and multidimensional. The authors particularly emphasise the benefits of adequate nutritional care and report improved progress in pressure ulcer healing in patients subjected to such measures [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The microvasculature under the small intestinal mucosa of patients with COVID-19 has serious inflammation and impaired digestion and absorption function, 5,6 which can not provide adequate nutrition for intestinal lymphocytes.Malnutrition can cause the decrease of systemic immune function. [34][35][36][37][38][39][40][41][42][43][44][45] More than 60% of patients with COVID-19 have lymphocytopenia,and almost all patients with COVID-19 have a decrease in the absolute number of T lymphocytes,CD4 + T cells and CD8 + T cells. [21][22][23][24][25][26][27][28][29][30][31][32][33] The negative nitrogen balance of patients with COVID-19 was 99.34%, and the proportion was consistent with the proportion of absolute number decrease of T lymphocytes,CD4 + T cells and CD8 + T cells in the literature.…”
Section: Comparison Of Prealbumin Between Two Groupsmentioning
confidence: 99%
“…In the later period of treatment the incidence of lymphocytopenia in the treatment group was significantly lower than that in the control group and literature reports.60% of human lymphocytes are distributed in the intestinal system.dipeptides and tripeptides can be actively absorbed,directly providing nutrition for intestinal lymphocytes,and improving the immune function of patients. [34][35][36][37][38][39][40][41][42][43][44][45] These changes of prealbumin and lymphocytopenia in the treatment group may be the reason that the rehabilitation speed of the treatment group is significantly faster than that of the control group.…”
Section: Comparison Of Prealbumin Between Two Groupsmentioning
confidence: 99%
“…Malnutrition is one of the well-known risk factors for the development of pressure ulcers in hospitals and nursing homes [12][13][14][15]. Similarly, Lizaka et al reported that malnutrition is a risk factor for the development of pressure ulcers in patients who are under home care follow-up [16].It has been shown that providing the necessary nutritional supplements after early detection of malnutrition reduces the development of pressure ulcers and increases the healing of existing pressure injuries [15]. Hydration and nutrition play an important role in skin and tissue vitality and aid in tissue repair in pressure ulcer management [14] Therefore, appropriate screening for nutritional status, collaboration with a specialist dietitian, and appropriate nutritional support should be important aspects of pressure wound management in patients at risk [17].In this study, we aimed to evaluate the clinical and demographic characteristics of the patients followed by the home care services unit of Kutahya Health Sciences University and to investigate the relationship between nutrition-related laboratory values and pressure ulcer grade.…”
Section: Introductionmentioning
confidence: 99%
“…Malnutrition is one of the well-known risk factors for the development of pressure ulcers in hospitals and nursing homes [12][13][14][15]. Similarly, Lizaka et al reported that malnutrition is a risk factor for the development of pressure ulcers in patients who are under home care follow-up [16].It has been shown that providing the necessary nutritional supplements after early detection of malnutrition reduces the development of pressure ulcers and increases the healing of existing pressure injuries [15].…”
Section: Introductionmentioning
confidence: 99%